Effect of Polymer–Fullerene Interaction on the Dielectric Properties of the Blend. Issue 13 (17th February 2017) - Constantinou, Iordania; Yi, Xueping; Shewmon, Nathan T.; Klump, Erik D.; Peng, Cheng; Garakyaraghi, Sofia; Lo, Chi Kin; Reynolds, John R.; Castellano, Felix N.; So, Franky
Abstract : It is commonly believed that large dielectric constants are required for efficient charge separation in polymer photovoltaic devices. However, many polymers used in high‐performance solar cells do not possess high dielectric constants. In this work, the effect of polymer–fullerene interactions on the dielectric environment of the active layer blend and the device performance for several donor–acceptor conjugated polymer systems is investigated. It is found that, while none of the high‐performing polymers studied has a dielectric constant value larger than 3, all polymer–fullerene blends have a significantly larger dielectric constant compared to their pristine constituents. Additionally, it is found that the blend dielectric constant reaches a maximum value in fully optimized devices. Using PTB7:PC71 BM blends as an example, it is showed that, in addition to a small increase in the dielectric constant, devices fabricated using the optimum processing additive concentration exhibit almost 3X larger excited state polarizability. This large increase in excited state polarizability results in a substantial difference in short‐circuit current and ultimately device performance. The results show that the excited state polarizability critically depends on polymer–fullerene interactions, and can be a leading indicator of device performance for a given material system. Abstract : The relationship between the dielectric constant and the device performance is investigated in polymer solar cells. The increase in the dielectric constant observed upon polymer–fullerene blending correlates well with device performance, in contrast to the pristine polymer dielectric constant. More importantly, the increase in excited state polarizability upon blending is a key indicator of device performance and is responsible for efficient charge transfer.